Antimicrobial Susceptibility of Urogenital and Extragenital Neisseria gonorrhoeae Isolates Among Men Who Have Sex With Men: Strengthening the US Response to Resistant Gonorrhea and Enhanced Gonococcal Isolate Surveillance Project, 2018 to 2019. Issue 12 (December 2021) - Quilter, Laura A.S.; St. Cyr, Sancta B.; Hong, Jaeyoung; Asbel, Lenore; Bautista, Ilene; Carter, Bonnie; Casimir, Yanick; Denny, Michael; Ervin, Melissa; Gomez, Raquel; Harvey, Alesia; Holderman, Justin L.; et al.
Abstract : Background: We investigated differences in gonococcal antimicrobial susceptibility by anatomic site among cisgender men who have sex with men (MSM) using specimens collected through the Centers for Disease Control and Prevention's enhanced Gonococcal Isolate Surveillance Project and Strengthening the US Response to Resistant Gonorrhea. Methods: During the period January 1, 2018–December 31, 2019, 12 enhanced Gonococcal Isolate Surveillance Project and 8 Strengthening the US Response to Resistant Gonorrhea sites collected urogenital, pharyngeal, and rectal isolates from cisgender MSM in sexually transmitted disease clinics. Gonococcal isolates were sent to regional laboratories for antimicrobial susceptibility testing by agar dilution. To account for correlated observations, linear mixed-effects models were used to calculate geometric mean minimum inhibitory concentrations (MICs), and mixed-effects logistic regression models were used to calculate the proportion of isolates with elevated or resistant MICs; comparisons were made across anatomic sites. Results: Participating clinics collected 3974 urethral, 1553 rectal, and 1049 pharyngeal isolates from 5456 unique cisgender MSM. There were no significant differences in the geometric mean MICs for azithromycin, ciprofloxacin, penicillin, and tetracycline by anatomic site. For cefixime and ceftriaxone, geometric mean MICs for pharyngeal isolates were higher compared with anogenital isolates ( P < 0.05). The proportion of isolates with elevated ceftriaxone MICs (≥0.125 μg/mL) at the pharynx (0.67%) was higher than at rectal (0.13%) and urethral (0.18%) sites ( P < 0.05). Conclusions: Based on data collected from multijurisdictional sentinel surveillance projects, antimicrobial susceptibility patterns of Neisseria gonorrhoeae isolates may differ among MSM at extragenital sites, particularly at the pharynx. Continued investigation into gonococcal susceptibility patterns by anatomic site may be an important strategy to monitor and detect the emergence of antimicrobial resistant gonorrhea over time. Abstract : We investigated anatomic site differences in patterns of antimicrobial susceptibility of Neisseria gonorrhoeae isolates collected from men who have sex with men attending sexually transmitted disease clinics in 2018 to 2019.Supplemental digital content is available in the text.